1976
DOI: 10.1073/pnas.73.4.1246
|View full text |Cite
|
Sign up to set email alerts
|

Antisera against electrophoretically purified tubulin stimulate colchicine-binding activity.

Abstract: Several rabbit antisera have been prepared against reduced and alkylated, electrophoretically purified tubulin isolated from chick brain. These antisera give a single precipitin line in Ouchterlony double diffusion plates when tested against partially purified tubulin, and label specifically microtubule-and tubulin-containing structures, such as mitotic spindles, cilia, and vinblastine-induced crystals, in a variety of cells. The same antisera also display the unique ability to stimulate the colchicine-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The microtubules, intermediate filaments, and microfilaments are the major components of the cytoskeleton in eukaryotic cells, and have not been shown to exist extracellularly in viable cells (Aubin et al, 1976;for reviews, see Aubin, 1981, also Weber and Osborn, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…The microtubules, intermediate filaments, and microfilaments are the major components of the cytoskeleton in eukaryotic cells, and have not been shown to exist extracellularly in viable cells (Aubin et al, 1976;for reviews, see Aubin, 1981, also Weber and Osborn, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…The antiserum obtained has been previously characterized (20,21) and reveals specific staining of mitotic spindles and other microtubule-containing structures.…”
Section: Resultsmentioning
confidence: 99%
“…Preimmune sera were obtained from the same animals prior to immunization. The preparation of antiserum to tubulin has been previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…This is in keeping with the generalized structural characteristics of numerous other processes, including those of osteocytes (Holtrop and Weinger, 1972) and the axons of neuronal cells (for review, see Lasek and Brady, 1981). Finally, after approximately 20 years of detailed ultrastructural analysis (Porter, 1966;Ishikawa et al 1969;for review, see Porter et al, 1983), and approximately ten years of investigation by immunofluorescence (Lazarides and Weber, 1974;Aubin et al, 1976;for review, see Aubin, 1981;Weber and Osborn, 1981), cytoskeletal elements have not been shown to penetrate extra~el lularly in viable cells. Thus, we have commenced by steppmg back from the functional and structural complexities and uniqueness of the odontoblast and its process, to apply techniques designed to delineate cyto-architectural components thought to be ubiquitous in all cells of higher organisms.…”
mentioning
confidence: 82%
“…As background. however, to the first specific application discussed here, it ĩ best~o dig~ess briefly to explain that antisera hav~been~repared m rabbits agam.st tubulin the major subunit protem of microtubules, The tubuhn had been electrophoretically-purified to reduce the number of contaminating 'polypeptides that typically co-purify with tubulin (Aubin et al, 1976;McKeithan and Rosenbaum, 1984). Antibodies specific for tubulin were affinity-purified from the antisera by chromatography on Sepharose 4B to which tubulin had been covalently coupled (Weber et al, 1975;Aubin, 1981).…”
mentioning
confidence: 99%